Heat Wave Trends in Southeast Asia: Comparison of Results From Observation and Reanalysis Data - Li, Xian‐Xiang; Yuan, Chao; Hang, Jian (Geophysical research letters, 2022)
Southeast Asia (SEA), a region climatologically important but limited by data availability, is suffering from serious scarceness of heat wave (HW) research. Using the observational and reanalysis data, we find that in most parts of SEA, HWs are becoming more frequent, longer‐lasting, and stronger, and affect more land areas. The increasing trends of HW characteristics defined by minimum temperatures are larger than those by maximum temperatures, alarming a situation of anomalously warm night. Magnitude of yearly hottest HW event increases faster, and duration of yearly longest HW shows significant trends in more areas than their average counterparts. ERA5 reproduces well the HW trends defined by daily minimum temperatures, but underestimate those by maximum temperature. The data set CHIRTS improves on daily maximum temperature and associated HW trends, but deteriorates on daily minimum temperature. This study highlights the importance of high‐quality data, either observational or reanalysis, on the HW study in SEA. Plain Language Summary Heat waves (HWs) are a series of days of extremely high temperatures. They can pose serious impacts on public health, for example, morbidity and mortality. Climate change makes HW events globally longer, more frequent, and more intensive. Southeast Asia is very vulnerable to HWs, but suffers from serious lack of HW research due to missing high‐quality and long‐term observational data in the region. We use an observational data set and two reanalysis data sets (combination of observational and modeling data) to analyze the HW trends during 1983–2016. We find that HWs defined by nighttime minimum temperatures increase faster than those by daytime maximum temperatures. Magnitude of yearly hottest HW event increases faster than average HW intensity, and duration of yearly longest HW shows significant trends in more areas than its average counterpart. The proportion of land areas affected by HW is increasing. One reanalysis data set can reproduce the HW trends defined by daily minimum temperatures when compared with the observational data, but underestimate the trends by daily maximum temperature. The other reanalysis data set shows better performance in HW trends by daily maximum temperature. This study highlights the importance of high‐quality data, either observational or reanalysis, for better understanding HW in Southeast Asia. Key Points Heat waves are becoming more frequent, longer‐lasting, and more intense in most parts of Southeast Asia and affect more land areas Yearly hottest heat wave (HW) magnitude increases faster and longest HW duration has significant trends in more areas than their average counterparts CHIRTS improves over ERA5 on daily maximum temperature and the associated HW trends, but deteriorates on daily minimum temperature